Successful treatment of a huge hepatic carcinoma with right portal vein thrombosis: A case report. Issue 17 (April 2020) - Tang, Kezhong; Zhang, Bo; Dong, Linping; Wang, Lantian; Jin, Yecheng; Tang, Zhe
Abstract: Introduction: Unlike the traditional associating liver partition and portal vein ligation for staged hepatectomy, it is still controversial whether patients with portal vein thrombosis can receive benefits from liver partition. Patient concerns: Right upper abdominal distension for 2 months. Diagnosis: Hepatocellular carcinoma with portal vein invasion Intervention: Radiofrequency-assisted liver partition with portal vein ligation (RALPP) Outcomes: Disease-free survival: 3 months, overall survival: 7 months Conclusion: Our results advocate this variation of RALPP for use in patients with huge HCC with portal vein invasion, without enough future liver remnant. Patients can receive benefits from the operation, including a shorter operation time, better recovery, and lower overall costs of the 2-stage procedure.